Exclusion of Known Protease Activated Receptors in Factor VIIa-induced Signal Transduction - Petersen, Lars C.; Thastrup, Ole; Hagel, Grith; Sørensen, Brit B.; Freskgård, Per-Ola; Rao, L. Vijaya M.; Ezban, Mirella (Thrombosis and Haemostasis, 2000)
The protease activity is mandatory for intracellular activities induced by coagulation factor VIIa (FVIIa), and in this way it resembles signal transduction induced by thrombin and trypsin caused by specific, proteolytic cleavage of protease activated receptors (PARs). The mechanism for FVIIa-induced signal transduction is, however, not known although a mechanism involving PAR cleavage has been deduced from studies of cytosolic Ca2+ release and p44/p42 mitogen activated protein kinase (MAPK) activation. In the present work we have examined the possibilities that i) FVIIa-induced signal transduction involves the activation of one of the four known PARs, or ii) exposure of cells to FVIIa releases a soluble ligand that is responsible for MAPK activation. For this purpose, we evaluated the effects of FVIIa, thrombin, FXa, trypsin and PAR agonist peptides on the Ca2+ release and MAPK activation in tissue factor-(TF) transfected baby hamster kidney (BHK[+TF]) cells and Madin-Darby canine kidney (MDCK) cells. FVIIa induced a significant MAPK signal in BHK(+TF) cells and in MDCK-I and -II cells whereas no MAPK activation was observed with thrombin, FXa or PAR agonist peptides. Thrombin, trypsin, PAR-1 and PAR-2 agonist peptides induced a prominent Ca2+ response in both cell types. In contrast the cells did not respond with a detectable Ca2+ signal when treated with FVIIa. These results suggest that the intracellular activity induced by FVIIa is distinctly different from that induced by trypsin, thrombin and FXa not involving any of the known PARs. Conditioned medium from BHK(+TF) cells treated with FVIIa failed to induce a MAPK response in untreated BHK(+TF) cells when FVIIa was removed by immunoadsorption from the medium prior to its transfer to the untreated BHK(+TF) cells. Although it is not possible entirely to exclude a transient response close to the cell surface, the data suggest that the intracellular response was not induced by an autocrine release of a soluble mediator to the medium.
Keywords: Factor VII; tissue factor; signal transduction; protease activated receptor; cytosolic Ca2+ mobilisation